2010
DOI: 10.1002/etc.331
|View full text |Cite
|
Sign up to set email alerts
|

Growth, abnormalities, and mortality of tadpoles of American toad exposed to combinations of malathion and nitrate

Abstract: American toad tadpoles (Bufo americanus) were exposed to malathion and nitrate in a fully factorial experiment that crossed four concentrations of malathion ranging between 0 and 1,000 µg malathion/L, and five concentrations of nitrate ranging from 0 to 16 mg NO(3) -N/L to identify single and interactive effects. In this 21-d experiment, we recorded tadpole length, mass, survivorship, and frequencies of diamond-shaped and stiff-tail abnormalities. Malathion increased frequency of diamond-shaped and stiff-tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…[13,[26][27][28] In the present study, individual effect of malathion at the tested concentrations revealed that the survivability of tadpoles was similar to that of the control (Figs. 1 and 2), thus this pesticide is less toxic to F. limnocharis even at ten times higher concentration of cypermethrin.…”
Section: Malathion Effect On Survivability and Time Of Metamorphosissupporting
confidence: 77%
See 2 more Smart Citations
“…[13,[26][27][28] In the present study, individual effect of malathion at the tested concentrations revealed that the survivability of tadpoles was similar to that of the control (Figs. 1 and 2), thus this pesticide is less toxic to F. limnocharis even at ten times higher concentration of cypermethrin.…”
Section: Malathion Effect On Survivability and Time Of Metamorphosissupporting
confidence: 77%
“…including atrazine, malathion, methyl parathion, carbaryl, chloropyrifos, cypermethrin, and diazinon) influence the amphibians, either singly or in combination; either directly or indirectly and produce a negative effect on growth and development. [6,[9][10][11][12][13] Response to the pesticide exposure is known to vary among different species. [10] Further, the adult population in agro-ecosystems showed many morphological abnormalities than that of adult amphibians in undisturbed habitats [14,15] indicating the degraded environmental health and severity of chemical contaminations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon the study of photographs it was possible to quote that the abnormalities observed were purely dependent on the concentration of exposed malathion. Some authors have earlier reported that malathion is known to cause negative effects on the survivability of amphibians (Webb and Crain, 2006;Mackey and Boone, 2009;Krishnamurthy and Smith, 2010). This however can be taken as a support for the present study.…”
Section: Discussionmentioning
confidence: 46%
“…Malathion was found to induce abnormalities in the head, trunk and tail in tadpoles of Microhyla ornata (Pawar, Ghate and Katdare 1983), bending of tails in Xenopus laevis (Webb 2003), and increased frequency of diamond-shaped stiff-tails in the toad Bufo americanus (Krishnamurthy and Smith 2010). Similarly, exposure of B. melanostictus, Polypedates cruciger and Rana clamitans larvae to OP diazinon leads to tail curving and bending (Harris et al 1998;Ratnasooriya 2008a, 2008b).…”
Section: Discussionmentioning
confidence: 92%